Analisis Fatwa DSN Nomor 123/DSN-MUI/XI/2018 tentang Dana TBDSP dalam Perspektif Sosiologi Hukum - Dery Ariswanto (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2021)
The purpose of this study is to analyze the Fatwa of the National Sharia Supervisory Board No: 123/DSN-MUI/XI/2018 according to sociology of law. This qualitative research uses descriptive-analysis method, which describes the management of TBDSP funds in the DSN fatwa, then it is analyzed using the sociology of law theory and this research uses a sociological-normative approach. The results of this study indicate that Fatwa No: 123/DSN-MUI/XI/2018 was made on the consideration that Islamic Financial Institutions in carrying out their activities need guidelines for using non-halal funds and there is no dhawabith and hudud regarding non-halal fund management. So that it became known the term TBDSP Fund, which means that non-halal funds obtained by Islamic Financial Institutions cannot be recognized as income. These funds must be channeled for social activities and must be separated into special accounts based on what is stated in the fatwa. Changes in regulations related to non-halal funds for Islamic Financial Institutions are influenced by social, economic, and scientific factors. So that the existence of a fatwa regarding the use of TBDSP funds can be said to be an answer to the need for change in Islamic Financial Institutions in terms of non-halal fund management. It should be that the DSN Fatwa regarding the use of TBDSP Funds can be applied by Islamic Financial Institutions and asks DPS in Sharia Financial Institutions to carry out maximum supervision.